Cultures of Taste/Theories of Appetite: Eating Romanticism - Morton, T. author. aut Link
XXII, 287 p. 4 illus.
Keywords: Cultures of Taste/Theories of Appetite brings two major critical impulses within the field of Romanticism to bear upon an important and growing field of research: appetite and its related discourses of taste and consumption. As consumption, in all its metaphorical variety, comes to displace the body as a theoritical site for challenging the distinction between inside and outside, food itself has attracted attention as a device to interrogate the rhetoric and politics of Romanticism. In brief, the volume initiates a dialogue between the cultural politics of food and eating, and the philosophical implications of ingestion, digestion and excretion.